Clarifying species identity in Aphanopus using wavelet-based otolith shape analysis - Joana Vasconcelos; Javier Martinez; Airam Guerra-Marrero; José Otero-Ferrer; Alba Jurado-Ruzafa; Ricardo Sousa; Carlos Hernández-González; Mafalda Freitas; Víctor M. Tuset (PLoS ONE, 2025)
Accurate species identification is crucial for effective fisheries management, particularly for cryptic species with overlapping ranges and similar morphologies. This study explores the coexistence and distribution of Aphanopus carbo and Aphanopus intermedius in the northeastern Atlantic over four decades using otolith contour analysis. Otolith samples were collected from Madeira and the African coast between 1990 and 2021 and analyzed using a wavelet-based method, which improves species discrimination by capturing finer morphological details. The analysis revealed stable species proportions over time, with A. carbo generally dominating the catches (~55–60%), except in 2010 when a decline was observed. A higher presence of A. intermedius in offshore areas may be associated with increased salinity near Madeira Island during the spawning season (October–December). Environmental changes, including variations in temperature and salinity at depths greater than 800 m, and the progressive expansion of the drifting longline fishery to new grounds, likely influenced these patterns. This study demonstrates that combining otolith contour analysis with genetically identified reference specimens enhances species discrimination and provides valuable insights into population dynamics and habitat use. These findings contribute to more effective fisheries management and stock assessments for these economically important scabbardfish in the northeastern Atlantic.